Algernon Sidney and the Republican heritage in England and America - Houston, Alan Craig, 1957- (Princeton University Press, 1991)
Alan Houston introduces a new level of rigor into contemporary debates over republicanism by providing the first complete account of the range, structure, and influence of the political writings of Algernon Sidney (1623-1683). Though not well known today, Sidney's Discourses Concerning Government influenced radicals in England and America throughout the eighteenth and nineteenth centuries. To many, it was a ""textbook of revolution."" Houston begins with a masterful intellectual biography tracing the development of Sidney's ideas in the political and intellectual context of Stuart England,
Based on the author's thesis.
Keywords: Sidney, Algernon, -- 1623-1683.; Sidney, Algernon, -- 1622-1683.; Sidney, Algernon, -- 1623-1683; HISTORY -- United States -- 19th Century.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.